Simultaneous Estimation of Nimesulide and Paracetamol in Tablets by Reverse Phase High Performance Liquid Chromatography - Nagoji, K.E.V.; Vijaya Srinivas, S.; Srinivasa Rao, S.; Patro, S.S. (Asian Journal of Chemistry, 2010)
A simple, precise, fast, reproducible and selective reverse phase HPLC method has been developed for the simultaneous estimation of nimesulide and paracetamol from tablets. The analyte was resolved by using a mobile phase (acetonitrile and water in the ratio 60 : 40) at a flow rate of 0.7 mL/min. on an isocratic HPLC system consisting of LC-10 AT liquid pump, SPD-10A UV-Visible detector, an ODS C-18 RP column (4.6 mm I.D. x 25 cm) at a wavelength of 230 nm. The linear dynamic range for both nimesulide and paracetamol was 0.25 to 40.0 μg/mL by this method. Ibuprofen was used as an internal standard.